Flavonoids of Neotorularia aculeolata Plant - Fatma A. Ahmed,; Inas M. Abd El–Wahab Khamis,; Samar Y. Desoukey, (Journal of Pharmacy and Nutrition Sciences, 2011)
Neotorularia aculeolata belongs to the family Cruciferae that has several uses in the Egyptian folk medicine for many years. Nothing could be traced about the chemical composition of the plant. Extraction, isolation and purification of the air-dried plant material using different chromatographic techniques (PC, TLC & CC) provided seven flavonoids. Identification of the isolated compounds using different chemical and physical techniques (UV, 1H-NMR and C 13 NMR spectroscopy) allowed to characterize these compounds as kaempferol, kaempferol-7-O-rhamnoglucoside Kaempferol-7-neohesperidoside, quercetin, rutin, quercetin-3-O- β-D-glucoside-7-O-α-L-rhamnoside-3`-methylether, quercetin-3,7-di-O-α-L-rhamnoside-3`-methylether and myricetin.